Optimalisasi Proses Produksi Celana Panjang Melalui Pendekatan Six Sigma - Ali Subhan (Jurnal Sistem dan Manajemen Industri, 2018)
PT. Tainan Enterprises Indonesia branch of Cianjur produce various kinds of garment products. One of the most widely product is trousers. The product are still many defects. This is showed from the number of defective products during February 2015 until mid-March 2015 which reached 509 products unit of 10.138 trousers produced. Therefore, appropriate quality control is required to optimize the quality of trousers products. This research method uses Six Sigma approach with DMAIC cycle (Define, Measure, Analyze, Improvement, Control). Based on the results of the research is known the most dominant type of defect is oblique belt loop and skid jump defects. Factors causing of oblique belt loop defects are sourced from human factors (operator does not follow signs and operators are fatigue), engine factor (old machine age and engine setting less than perfect), material factor (needle material less reliable and materials need to be heating which is high), and the method factor (information on working methods is still lacking). While the factors causing of skid jump defects are sourced from human factors (operator is less careful in choosing to sewing needles and operators experience fatigue), machine factor (old machine age and no regular machine maintenance), material factor (needle less reliable sewing), and method factors (production supervision and quality control are still weak). Quality Increasing could be can increase the value of Six sigma from 3.82 to 4.27.